PENGEMBANGAN BAHAN AJAR MENULIS PETUNJUK BERBASIS MODEL PEMBELAJARAN PENINGKATAN KEMAMPUAN BERPIKIR DI KELAS IV SEKOLAH DASAR - Refiarni Refiarni (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2018)
This research is based on the existence of teaching materials that are not in accordance with the demands of basic competencies (KD) in the applicable curriculum, the teaching materials used do not contain the stages of writing and teaching materials also do not use appropriate strategies in learning to write instruction. The aim to be achieved in the development of this material is to produce valid, practical and effective instructional materials for written instruction. This type of research is a development research that uses a 4-D model consisting of four phases: defining (defining), design (design), development (developing), and distribution (spread). Test the validity of the research obtained through materialized lesson plans, assessment of teacher responses and assessment of students' responses. see the effectiveness of activities, the assessment process and the results of written instructions. The results showed that learning to write instruction based on the MP PKB learning model improved thinking skills to help students understand the stages of the instruction writing process. Based on these results, it was concluded that the teaching materials for writing instruction based on the improved learning model of thinking ability for fourth grade students developed could be considered valid, practical, and effective.